Catholic religious perspective on caste culture or marriage of Endogamy Rang in Bajawa, East Nusa Tenggara - rasdi, Rasdiansyah; Maria Lusiana Magho; Renadya Maharani; Tyrese Alvionda (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Caste culture or endogamous marriages that still occur in Bajawa, East Nusa Tenggara is a social phenomenon that is complex and requires deep understanding from a religious perspective, including Catholicism. The marriage system of the Bajawa people in Indonesia is endogamous marriages of people or castes of people (social strata) based on people (social strata) and are passed down from generation to generation. Endogamy rang is marrying someone from within same group or caste. For the people of Bajawa Rang is something that is seen as an identity that is firmly held and has the namely nature of authenticity. The Bajawa indigenous people differentiate people into three, gae, kisa and riwu azi/ho'o. Catholic church teaches that all human beings are created equal before God and not may be distinguished by caste or race. Hence, the practice of marriage endogamy which limits life partners based on caste or ethnicity is not appropriate with Church teachings. In the context of marriage in Bajawa, which involves the practice of endogamy, The church encourages couples to consider marrying in outside their group. However, the Church also emphasizes its importance complete freedom and agreement in the decision to marry, and not to be imposing certain views on couples who choose to marry in their group. In the context of Bajawa culture, which still maintains caste traditions or endogamous marriage, the Catholic Church can act as an agent of change which promotes equality and unity among people. Church can teaches Christian values ​​that protect human dignity and appreciate cultural diversity, so as to create harmony and unity among all people. The purpose of this study was to find out the perspective and role of Catholicism regarding caste culture or endogamous marriage in Bajawa. The research method used is a qualitative method because it is descriptive. This research is a type of normative legal research, meaning that the study is limited to applicable law. The approach in this study is based norms or statutory approaches where conditions or based on real conditions that occur in society.